2012
DOI: 10.1016/j.physrep.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative quantum gravity

Abstract: Asymptotic safety describes a scenario in which general relativity can be quantized as a conventional field theory, despite being nonrenormalizable when expanding it around a fixed background geometry. It is formulated in the framework of the Wilsonian renormalization group and relies crucially on the existence of an ultraviolet fixed point, for which evidence has been found using renormalization group equations in the continuum."Causal Dynamical Triangulations" (CDT) is a concrete research program to obtain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
698
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(708 citation statements)
references
References 201 publications
10
698
0
Order By: Relevance
“…In earlier work [100][101][102] indications were found that suggest that Quantum Einstein Gravity in the continuum formulation based upon the EAA might be related to the discrete approach employing Causal Dynamical Triangulation [79,103]. In particular, the respective predictions for the fractal dimensions of spacetime were compared in detail and turned out similar [101,102].…”
Section: Comparison With Monte Carlo Resultsmentioning
confidence: 94%
“…In earlier work [100][101][102] indications were found that suggest that Quantum Einstein Gravity in the continuum formulation based upon the EAA might be related to the discrete approach employing Causal Dynamical Triangulation [79,103]. In particular, the respective predictions for the fractal dimensions of spacetime were compared in detail and turned out similar [101,102].…”
Section: Comparison With Monte Carlo Resultsmentioning
confidence: 94%
“…The building blocks of the piecewise linear geometries used in dynamical triangulations are identical, equilateral 5 four-simplices, which by assumption are everywhere flat on the inside, like the building blocks of Regge calculus [17]. When these building blocks are glued together along identical boundary three-simplices or "faces" to construct a four-dimensional piecewise flat manifold, curvature will generically appear in a singular fashion along the two-dimensional subsimplices of the triangulation, the triangles or "hinges.…”
Section: Holonomies In Dynamical Triangulationsmentioning
confidence: 99%
“…More complete descriptions can be found elsewhere; see [5] and references therein. In standard CDT, each spacetime T has a proper-time slicing with integer label t, and is assembled from four-simplices in a layered fashion, 12 where one layer of thickness Δt ¼ 1 is a piecewise flat piece of spacetime of topology S 3 × I, all of whose vertices are contained in either of its spatial boundary submanifolds at times t or t þ 1.…”
Section: Wilson Lines In Cdtmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more detailed description of the CDT construction we refer the interested reader to [22,23,24].…”
mentioning
confidence: 99%